YOGHURT FORMULATION FROM RED DRAGON FRUIT AND ACTIVITY TEST AGAINST PATHOGENIC BACTERIA - Asiska Permata Dewi; Dinda Musdalifah; Alfin Surya; Fahma Shufyani (Ensiklopedia of Journal, 2025)
The dairy product known as yogurt is fermented by lactic acid bacteria. The purpose of this study is to evaluate the properties and antibacterial activity of yogurt at concentrations of 0%, 10%, 20%, and 30% against harmful bacteria, specifically Escherichia coli and Bacillus subtilis. The properties were examined for lactic acid bacteria, viscosity, pH, hedonic value, and organoleptic features. The disk diffusion method was used to test the antibacterial activity. According to the findings of evaluating the yogurt's organoleptic properties, every formula was homogenous, thick, sour-tasting, and pink. The range of the viscosity values is 412 cP to 972 cP. The lactic acid bacteria vary from 6.8x10^9 to 9.0x10^9, and the pH levels fall between 4.26 and 4.42. In contrast, F3 was the most favored formula in the hedonic test. Following that, the average inhibition zones for the antibacterial activity of yogurt against E. coli bacteria at concentrations of 0%, 10%, 20%, and 30% were 7.5 mm, 9.9 mm, 11.2 mm, and 12.2 mm, respectively. In contrast, the inhibition zone diameters against B. subtilis bacteria were 7.4 mm, 9.8 mm, 13.1 mm, and 14.4 mm. A p-value of less than 0.05 indicated a statistically significant difference in antibacterial activity tests. Red dragon fruit yogurt shows antibacterial action against B. subtilis and E. coli, according to the diameter of the inhibition zone that was obtained.. Keywords: yoghurt, red dragon fruit peel, antibacterial activity, E. coli, B. Subtilis